Chemical studies of chromone derivatives - Sabbagh, Liezel Veronica (Rhodes University, Faculty of Science, Department of Chemistry, 2001)
This study has focussed on several aspects of chromone chemistry, viz., (i) the influence of remote substituents on the basicity of 2-(N,N-dimethylamino)chromones, (ii) MoritaBaylis-Hillman reactions of substituted chromone-3-carbaldehydes and (iii) an investigation into the application of chromone chemistry in the total synthesis of the marine natural product, Rietone A. Selected 2-(N,N-dimethylamino )chromones were prepared using two different methods; firstly, via cyclisation of salicylate-derived N,N-dimethyl-3;.(2-hydroxyphenyl)-3- oxopropanamide precursors and, secondly, via 2-hydroxyacetophenone boron difluoride complexes. Â¹Â³C NMR analysis of the 6- and 7-methoxy-2-(N,N-dimethylamino)chromones confirmed that protonation occurs at the chromone carbonyl oxygen rather than the amino nitrogen - a conclusion supported by mol~cular orbital calculations. Potentiometric analysis of 2-(N,N-dimethylamino )chromones in ethanol-water afforded pKa (pK [subscript a]) values in the range 2.22 - 2.52. The observed trend has been rationalised in terms of substituent effects with the aid of molecular orbital calculations at the semi-empirical and ab initio levels, while hydrogen-bonding effects have been used to account for the apparently anomalous result obtained for the 6-nitro derivative. A series of seven substituted chromone-3-carbaldehydes, prepared by the application of Vilsmeier-Haack methodology to the corresponding 2-hydroxyacetophenones, have been examined as substrates for Morita-Baylis-Hillman reactions, using DABCO as the catalyst and three different activated alkenes, viz., methyl acrylate, methyl vinyl ketone and acrylonitrile. In all cases, with the exception of 6-nitrochromone-3-carbaldehyde, the reactions have been shown to afford the expected Morita-Baylis-Hillman products. Use of methyl acrylate and methyl vinyl ketone as the activated alkene has been observed to afford additional, unprecedented dimeric products, which have been unambiguously characterised using a combination of single crystal X-ray analysis and spectroscopic (high resolution MS and NMR) techniques. Different dimer-like adducts have been isolated from reactions in which acrylonitrile was used as the activated alkene, and the structures of these novel products have-been determined <spectroscopically. Tentative mechanistic rationalisations for the formation of the "dimeric" products have been presented. Optimisation studies, aimed at improving the yields of the Morita-Baylis-Hillman products, have resulted in significant increases in conversion efficiency (up to 95%). It has also been shown that the Morita-Baylis-Hillman products may be readily converted to the corresponding "dimers". An exploratory study into the synthesis of Rietone A has been initiated. Ring-opening of a chromone derivative was expected to provide access to the aromatic moiety, while retrosynthetic analysis of the aliphatic side chain suggested possible strategies for its construction. These approaches have proved largely unsuccessful, but preliminary studies involving Fries rearrangement of 4-(carbomethoxymethyl)phenyl 3,7-dimethyl-2,6-octadienoate appear to hold some promise for future development.
Keywords: Benzopyrans; Heterocyclic compounds -- Derivatives; Coumarins